2018
DOI: 10.1186/s12199-018-0750-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries and associated factors among primary school children: a population-based cross-sectional study in Riyadh, Saudi Arabia

Abstract: BackgroundDental caries is a preventable childhood disease, but public health efforts are hampered due to limited information on associated factors in vulnerable populations. Our study was aimed at estimating the prevalence of dental caries and identifying key associated factors in four major risk domains, including socioeconomic factors, child oral health behavior and practices, child feeding practices, and dietary habits among primary school children in Saudi Arabia.MethodsA cross-sectional study design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
120
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 46 publications
18
120
4
1
Order By: Relevance
“…Studies of Veterans with HPV+ OPSCC have quantified tobacco exposure as high as 150 PY [ 8 ]. Although smoking rates have decreased over the last two decades, evidence suggests that tobacco exposure remains a significant consideration for OPSCC patients throughout the United States and varies widely based on race/ethnicity and socioeconomic strata [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Veterans with HPV+ OPSCC have quantified tobacco exposure as high as 150 PY [ 8 ]. Although smoking rates have decreased over the last two decades, evidence suggests that tobacco exposure remains a significant consideration for OPSCC patients throughout the United States and varies widely based on race/ethnicity and socioeconomic strata [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 9 Unfortunately, knowledge gaps concerning the availability of baseline data on oral health and population-specific key modifiable factors for dental caries restrict the ability of many developing nations and semi-developed countries, including Saudi Arabia, to achieve the goals set by WHO. 10 Most importantly, caries affecting deciduous tooth is known as early childhood caries (ECC). This is one of the major concerning factors regarding the oral health of growing kids.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric dentistry organizations, such as the American Academy of Paediatric Dentistry and the Japanese Society of Paediatric Dentistry, referred to breastfeeding as a potential risk for ECC in their policy statements. 9 , 10 Whereas, reviews of epidemiological studies have found the relationship between breastfeeding and ECC to be inconclusive. 11 , 12 A few studies suggest that breastfeeding may promote dental caries 13 – 15 while other studies have not found any association.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although smoking rates have decreased over the last 2 decades, evidence suggests that tobacco exposure remains a signi cant consideration for OPSCC patients throughout the United States and varies widely based on race/ethnicity and socioeconomic strata. 3,9 The recent changes to the AJCC staging system for OPSCC make urgent the need to better de ne the potential impact of tobacco exposure on clinical outcomes for HPV+ OPSCC patients to appropriately counsel patients. Furthermore, given continued efforts at treatment de-escalation for HPV+ OPSCC tumors, it is critical to determine whether a subset of patients may be at risk for inappropriate deescalation.…”
Section: Introductionmentioning
confidence: 99%